Analysing Contemporary Land Tenure and the Impact of Land Reforms on Rural Peoples ‘Livelihoods in Customary Land: A Case of Zambia - CHANDA MWAMBA (2024)
This thesis delves into the state of contemporary customary land tenure security in Zambia, where the security of land tenure among rural smallholders or households plays a pivotal role in enhancing agricultural productivity. Notably, the land is steadily transitioning out of the customary system in Zambia, driven by both domestic and foreign actors acquiring large-scale holdings for export-oriented agriculture. The 1995 Land Act, which promoted land privatisation and formalisation, has expedited the commodification of customary land. This has given rise to informal and covert land markets characterised by corrupt transactions, effectively placing land out of reach for the impoverished and vulnerable rural population. This situation persists, even though land laws in Zambia explicitly prohibit the sale of customary land. Additionally, shifting political and socio-economic conditions are facilitating a move from communal to private property, predominantly leasehold regimes. The consequences of recent legal reforms on the structure of agrarian society remain to be fully comprehended. This thesis undertakes a comprehensive review of the transformation of customary tenure systems, shedding light on their repercussions for rural Zambians. It underscores the concept of the 'tragedy of the commons,' offering an alternative perspective alongside private ownership and government control. This thesis essentially aims to furnish evidence from a case study, scrutinising the prevailing legal framework and institutions governing customary land tenure and tenure security in Zambia, with a specific focus on the Chembe and Monze regions. This case study elucidates how land conflicts compromise land tenure security and impact the livelihoods of rural communities dependent on land-related activities. The research findings unequivocally reveal that land conflicts and tenure insecurity in Zambia stem from inherent deficiencies within land governance systems. These include a flawed legal and institutional framework and sub-optimal land allocation procedures. The repercussions of these issues extend to include loss of life and property damage. Consequently, this study posits a novel framework designed to enhance and safeguard land rights, improve land governance, and lay the groundwork for the implementation of such a framework in Zambia and other African nations. Profound insights into the land governance system and practices are imperative for devising equitable and effective solutions.